(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article analyzes the issues of marketing strategies for food products in the domestic market and ensuring price stability. Ways to achieve socio-economic stability by ensuring food security, meeting consumer needs, developing market infrastructure, and reducing price volatility were considered. The use of effective marketing tools in a competitive environment, strengthening cooperation between manufacturers and distributors, and price regulation mechanisms used by the state were also analyzed.